Ahiflower oil: A novel non‐GM plant‐based omega‐3+6 source. Issue 9 (September 2015) - Cumberford, Greg; Hebard, Andrew
<x xml:space="preserve">Abstract</x> Ahiflower oil, a novel and proprietary dietary oil with the richest effective combined essential fatty acids from a single non‐GM plant, has been developed agronomically in a unique vertically integrated "soil to oil" model at commercial scale by Nature's Crops International. Ahiflower oil helps resolve a persistent dilemma in sustainable global omega‐3 nutrition from marine sources while dramatically improving dietary omega‐3 EPA conversion from plant sources and while supplying beneficial anti‐inflammatory GLA not found in fish or algal oils. Having achieved key regulatory clearances in the US and EU, Ahiflower oil is launching in the latter half of 2015 in supplements and foods.